THE EFFECTIVENESS OF WORDWALL IN ENHANCING ENGLISH VOCABULARY MASTERY AMONG HIGH SCHOOL STUDENTS’ (AN EXPERIMENTAL RESEARCH AT SMAN 1 BILUHU) - Ntuiyo, Mohamad Akmal R.; Otoluwa, Moon Hidayati; Hatibie, Yunita (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
This research investigates the effectiveness of Wordwall as a learning media in enhancing English vocabulary mastery among first-grade students at SMAN 1 Biluhu. The background stems from students’ low vocabulary performance and the limited use of educational technology in the classroom. Employing a quasi-experimental design with one-group pre-test and post-test, the study involved 30 students and focused on four vocabulary categories: nouns, verbs, adjectives, and adverbs. The treatment consisted of four meetings using descriptive texts and Wordwall games. Data collection was conducted through vocabulary tests and analyzed using statistical methods including validity, reliability, normality, and paired sample t-test. The findings showed a significant improvement in students’ vocabulary scores after the intervention, with the average score increasing from 49 (pre-test) to 65 (post-test). The hypothesis testing also supported the effectiveness of Wordwall, with a p-value of 0.001 (< 0.05), indicating that the media significantly enhanced vocabulary mastery. Additionally, students demonstrated increased motivation and engagement during the learning process. Despite challenges such as limited internet access and varying student proficiency, the study concludes that Wordwall is a beneficial and interactive tool for vocabulary development. These results are expected to inform future instructional practices and promote the integration of digital tools in language education.